Pengaruh Beban Tugas Akademik Terhadap Tingkat Stres Mahasiswa Fakultas Dakwah dan Ilmu Komunikasi UIN Syarif Hidayatullah Jakarta - Irvanti, Risyanka Nafishafara; Khairunnisa, Zahra; N, Nurhasanah; Kosasi, Ferdiansyah Ishaq (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Academic stress is a form of psychological pressure that arises due to an imbalance between the demands of lectures and the ability of individuals to meet these demands. This study aims to determine the effect of academic task load on the stress level of students of the Faculty of Da’wah and Communication Sciences of UIN Syarif Hidayatullah Jakarta. This research uses a quantitative approach with descriptive methods, and involves 41 students as respondents selected by purposive sampling technique. Data instruments in the form of questionnaires have been tested for validity and reliability. The results of this study show that there is a significant influence between academic task load on student stress levels. R Square is 0.527, which means that the academic task load contributes 52.7% to the stress level of students, while the remaining 47.3% is influenced by other factors outside the X variable.